Analisis Efektivitas Anggaran Dan Pengendalian Biaya Pada PT Indofood Sukses Makmur Tbk - Galih Thoriq Murdianto; Khaerul Imam Mubaroq; Chyntia Novita Br Simangunsong; Muhamad Syahwildan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Budget management and cost control plays an important role in ensuring the smooth and sustainability of operational activities, especially in the food and beverage industry sector which has challenges in the form of fluctuations in raw material prices and high market competitions. This study aims to evaluate the effectiveness of budgeting and implementation of cost control at PT Indofood Sukses Makmur Tbk. The approach used is quantitative descriptive, through a budget analysis (budget variance analysis) and structured internal internal interviews in financial management. Data analyzed were sourced from the annual financial statements, budget documents, and the realization of operational expenditure over the past three years. This study aims to identify weak points in the budgeting process and compile relevant recommendations to improve cost efficiency and the accuracy of financial planning. The results of this study are expected to provide practical benefits for companies in improving the budget management system and cost, as well as an academic reference in the development of financial studies in the national manufacturing sector.